2020
DOI: 10.1002/art.41424
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Malondialdehyde–Acetaldehyde Are Detected Prior to Rheumatoid Arthritis Diagnosis and After Other Disease Specific Autoantibodies

Abstract: Objective To examine serum autoantibodies to malondialdehyde–acetaldehyde (MAA) prior to rheumatoid arthritis (RA) diagnosis. Methods Concentrations of anti‐MAA antibody isotypes, anti–cyclic citrullinated peptide 2 (anti–CCP‐2), and IgM rheumatoid factor (IgM‐RF) were evaluated before and after RA diagnosis in samples from cases (n = 214) and controls (n = 210). The timing of elevations in autoantibody concentrations relative to RA diagnosis was explored using separate mixed models for each antibody and/or is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 10 publications
1
45
0
1
Order By: Relevance
“…This was different from anti-acetylated histone antibodies that were increased in the RA-risk population and may follow a similar pattern as has been reported for ACPA fine-specificities and carbamylation reactivity that can arise years before RA onset ( 78 81 ). However, a recent report has shown that anti-MAA can be elevated before onset of RA disease but that the increase in levels occurs later in the pre-clinical phase than other autoantibodies ( 82 ). Our previous data demonstrate that certain anti-MDA/MAA clones but not others may contribute to RA pathogenesis by osteoclast activation ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was different from anti-acetylated histone antibodies that were increased in the RA-risk population and may follow a similar pattern as has been reported for ACPA fine-specificities and carbamylation reactivity that can arise years before RA onset ( 78 81 ). However, a recent report has shown that anti-MAA can be elevated before onset of RA disease but that the increase in levels occurs later in the pre-clinical phase than other autoantibodies ( 82 ). Our previous data demonstrate that certain anti-MDA/MAA clones but not others may contribute to RA pathogenesis by osteoclast activation ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…As they appear later in the preclinical course than anti-citrullinated protein antibodies or rheumatoid factor do, the authors proposed that malondialdehyde-acetaldehyde adduct formation and antimalondialdehyde-acetaldehyde immune responses could play a role in the transition from subclinical autoimmunity to clinically apparent arthritis. 92 Notably, malondialdehyde-acetaldehydemodified proteins have been found in inflamed periodontal tissue as they are generated as a result of inflammation-associated oxidative stress. However, because current data suggest that antimalondialdehyde-acetaldehyde autoantibodies may play a role in the development of rheumatoid arthritis, further investigations are needed.…”
Section: Posttranslational Modified Proteinsmentioning
confidence: 99%
“…IgG and immunoglobulin A anti–malondialdehyde‐acetaldehyde autoantibodies were detected in rheumatoid arthritis patients prior to clinical diagnosis. As they appear later in the preclinical course than anti–citrullinated protein antibodies or rheumatoid factor do, the authors proposed that malondialdehyde‐acetaldehyde adduct formation and anti–malondialdehyde‐acetaldehyde immune responses could play a role in the transition from subclinical autoimmunity to clinically apparent arthritis 92 . Notably, malondialdehyde‐acetaldehyde–modified proteins have been found in inflamed periodontal tissue as they are generated as a result of inflammation‐associated oxidative stress.…”
Section: Molecular Mechanism Of Periodontal Diseases‐induced Rheumato...mentioning
confidence: 99%
“…Antibodies against products of lipid degradation, malondialdehyde (MDA) and malondialdehyde-acetaldehyde (MAA) are increased in RA and show some association to RF and ACPA (62). The levels increase before diagnosis of RA, albeit at a later stage than RF and ACPA (63). Antibodies against the immunoglobulin binding stress protein BiP have been found in sera both from RA patients and asymptomatic subjects subsequently developing RA (64); but a recent meta-analysis showed only moderate diagnostic sensitivity (65).…”
Section: Non-criteria Autoantibodies In Ramentioning
confidence: 99%